The Effects of Earning Management and Environmental, Social, Governance (ESG) on Tax Avoidance with Leverage as A Moderating Variable - Arja Sadjiarto; Jonathan Alvin Ringoman; Leoni Angela (International Journal of Organizational Behavior and Policy, 2024)
The aim of this study is to determine effect of earning management and ESG on tax avoidance (TA) using leverage as a moderating variable. The underlying theories are stakeholder theory and agency theory. Samples of this study are 29 emitent listed on the IDX for the period 2018 - 2022. Earning management is measured using discretionary accrual with the Modified Jones Model method. ESG is measured by ESG score obtained from Refinitiv data. This research uses multiple linear regression by utilizing the Stata program. It is found that earning management does not have an effect on tax avoidance. ESG has an effect on tax avoidance. Leverage does not moderate the effect of earning management and ESG on tax avoidance.